The effect of DNA structure and restriction enzymes on transformation efficiencies in Neurospora crassa - Kristina Garnand; Mary Anne Nelson (Fungal Genetics Reports, 1995)
Addition of the appropriate restriction enzyme to linearized transforming DNA has been shown to increase transformation efficiencies in organisms as diverse as Saccharomyces cerevisiae (Schiestl and Petes 1991 Proc. Nat. Acad. Sci. USA 88:7585-7589) and Dictyostelium discoideum (Kuspa and Loomis 1992 Proc. Nat. Acad. Sci. USA 89:8803- 8807). This process has been described as REMI, for restriction enzyme-mediated integration. We have examined the effect of restriction enzyme addition on transformation efficiencies in Neurospora crassa. The frequency of cotransformation of a qa-2 inl double mutant with two plasmids [one containing the selectable marker qa-2+ (quinate utilization) and the other containing inl+ (inositol)] was also examined, as was the generation of stable versus abortive transformants.